Droop-based active voltage regulation control and robust stability analysis for VSCs in the large-scale RES-integrated power system - Zhao, Zhengkui; Su, Xiaoling; Yang, Jun; Zhou, Peng; Chen, Hui; Lu, Guoqiang (Frontiers in Energy Research, 2022)
New features like high penetration level, low inertia, weak damping is decreasing voltage support capacity in power system as it sees large-scale renewable energy sources (RESs) integration continuously. The reasonable solution to this challenge is developing additional active voltage regulation function for voltage source converters (VSCs). This paper proposes a droop-based active voltage control strategy for VSCs in large-scale RESs integrated power system to make VSCs continue to operate and regulate voltage at the point of common coupling (PCC) during a fault without causing overcurrent. In order to meet the requirements of RESs and Grid Code, all control boundary conditions are designed based on practical engineering data. Meanwhile, plant uncertainty and parameter disturbance is introduced into robust stability margin analysis model based on component connection method (CCM) and structured singular value (SSV) to improve the engineering application prospect. The effectiveness and feasibility of this control strategy is proved by logical deduction and practical simulation based on generalized small-signal model.